2015
DOI: 10.1186/s12865-015-0097-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RORγt activity and Th17 differentiation by a set of novel compounds

Abstract: BackgroundRetinoic acid receptor-related orphan receptor gamma t (RORγt) is the master regulator of Th17 cell differentiation, which plays a critical role in the pathology of several autoimmune diseases. By directing Th17 cells function, RORγt could be a potential target for drug development for Th17 related autoimmune disease.MethodsA Jurkat cell-based reporter assay system was used for screening RORγt inhibitors from a drug-like chemical library, following with mouse Th17 cells differentiation study to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Our results are consistent with other findings that resveratrol possesses anti‐inflammatory properties, explicitly on suppressing pro‐inflammatory cytokines and the recruitment of immune cells . Accumulating evidence has shown that RORγt plays a crucial role in the differentiation of T‐helper 17 (Th17) cells, pathogenesis of autoimmune diseases as well as maintenance and augmentation of chronic inflammations . In our Jurkat cell‐based reporter assay, resveratrol notably attenuated the RORγt promoter activity at noncytotoxic concentrations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with other findings that resveratrol possesses anti‐inflammatory properties, explicitly on suppressing pro‐inflammatory cytokines and the recruitment of immune cells . Accumulating evidence has shown that RORγt plays a crucial role in the differentiation of T‐helper 17 (Th17) cells, pathogenesis of autoimmune diseases as well as maintenance and augmentation of chronic inflammations . In our Jurkat cell‐based reporter assay, resveratrol notably attenuated the RORγt promoter activity at noncytotoxic concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…RORγt + ‐Jurkat stable cells were kindly provided by Prof. Z. Huang from Sun Yat‐sen University, Guangdong, China, and suspended in RPMI‐1640 medium (Gibco) supplemented with 10% FBS, 1% sodium pyruvate (Gibco), 1% MEM non‐essential amino acid solution (Gibco), 0.1% β‐mercaptoethanol (Sigma–Aldrich), and 1% penicillin/streptomycin solution (Gibco) . Upon assay, cells were seeded in 96‐well plates (8 × 10 5 cells mL –1 ) in complete medium overnight, and subsequently incubated with 50 μ m of trans ‐resveratrol, ascorbic acid (Abcam), butylated hydroxyanisole (Abcam), or 0.5% DMSO for 6 h while 0.5% DMSO was served as the control.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, there are no studies evaluating VEGF‐A after the treatments established in our study, neither in these cells. According to Liu et al and Ding et al IL‐17 could modulate angiogenesis directly (through IL‐17R binding on endothelial cells), or indirectly, by modulating cancer cell, and possibly other cells in the surrounding tumour stroma, to produce angiogenic factors. Maniati and Hagemenn demonstrated that synthetic IL‐17A can induce the expression of the pro‐angiogenic factors VEGF, PLAU, NRP2, IL‐6 and ID3 in colorectal cancer cells, as determined by qRT‐PCR and ELISA of conditioned media.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of AOA is shown in Figure 1(a). In previous studies, we established a stable ROR γ t-Jurkat cell line to test the activity of ROR γ t antagonists [24]. In this study, AOA exhibited potent inhibitory effects on ROR γ t transcription activity, with an EC50 value of 0.9483 μ M (Figure 1(b)).…”
Section: Resultsmentioning
confidence: 80%